Patio and pavilion : the place of sculpture in modern architecture - Curtis, Penelope (London : Ridinghouse ; Los Angeles : J. Paul Getty Museum, 2007)
This book examines the relationship between modern sculpture and architecture, an interplay that has laid the ground for the semi-sculptural or semi-architectural works by architects such as Frank Gehry and artists such as Dan Graham. The first half of the book looks at how the addition of sculpture enhanced several architectural projects, including Mies van der Rohe's ... more »Barcelona Pavilion (1929) and Eliel Saarinen's Cranbrook Campus (1934). The second half of the book uses several additional case studies, including Philip Johnson's sculpture court for New York's Museum of Modern Art (1953), to explore what architectural spaces can add to the sculpture they are designed to contain.
boek